(untitled) (Bangladesh Journal of Medical Science, 2022)
Oral administration of colostrum in premature infants has become increasingly common in recent years. Evidence-based studies emphasize that oral administration of colostrum supports immune development in low-birth-weight infants and premature newborns, contributing to the oral microbiota development and reducing the length of stay in hospital. However, its effects on breastfeeding are still not clearly known.This study examines the effect of oral colostrum, which is administered from the first 24 hours of life to the first breast-feeding, on first breast-feeding in very low-birth-weight premature infants who cannot be fed orally. By examining a total of four cases, this study has shown that oral administration of colostrum can be used to increase the success of first breastfeeding. This practice may provide hope for medically vulnerable lowbirth- weight infants,who cannot be fed orally, to benefit more from breast milk. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 912-917